Dampak Suasana Toko, Variasi Produk dan Kualitas Layanan terhadap Kepuasan Pelanggan di Kedai Kopi Kopiah Ireng Kabupaten Nganjuk - Muhammad Wahyu Aji Saputra; Risdiana Himmati; Moh Rois Abin (Journal of Economics Business Finance and Accounting, 2024)
The coffee shop industry represents a promising business sector. With the growing intensity of competition within this industry, businesses must prioritize enhancing customer satisfaction to sustain their competitive advantage. This research seeks to examine the influence of store atmosphere, product variiety, and serviice quality on customer satisfaction at Kopiah Ireng Coffee Shop, located in Nganjuk Regency. A quantitative research approach was employed, utilizing non-probability sampling. The study involved a sample of 100 customers from Kopiah Ireng Coffee Shop. Data were gathered through questionnaires and analyzed using multiple linear regression test, classical assumption test, and hypothesis testi methods with on aid of SPSS version 30.0. The results demonstrate that both individually and collectively, store atmosphere, product variety, and serviice quality exert a significant and positive influence on customer satisfaction. These findings confirm that these These factors significantly influence the increase in customer satisfaction at Kopiah Ireng Coffee Shop, Nganjuk Regency.